Engineering identity and communication outcomes: comparing integrated engineering and traditional public-speaking courses. Issue 3 (3rd July 2019) - Linvill, Darren L.; Tallapragada, Meghnaa; Kaye, Nigel B.
ABSTRACT: We assessed the effectiveness of an integrated engineering public-speaking class relative to a traditionally taught public-speaking class. The integrated class was designed to meet the growing science, technology, engineering, and mathematics communication needs and the fundamental Accreditation Board for Engineering and Technology and the National Communication Association student outcomes related to public speaking. Working within the Communication in the Disciplines theoretical framework, this study employed a quasi-experiment with both a test (engineering specific communication class) and control (traditional communication class) group; finding a significant increase with respect to attitude toward communication for students before and after the engineering specific class compared with the traditional class. Along with attitude toward communication, efficacy toward communication and being enrolled in the engineering specific class related positively to a sense of engineering identity for students at the end of class. For students enrolled in the engineering specific class, their sense of engineering identity was mediated through an improved attitude toward communication.